Assessment of aircraft dynamic characteristics in air manoeuvring - Кудиненко, А. В.; Котляров, В. П. (Proceedings of National Aviation University (archive), 1999)
Considered are analytical approach to the assessment of dynamic peculiarities of aircraft manoeuvring in wide range of parameters of their movement